2018
DOI: 10.1080/09537104.2018.1535703
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPases in platelet membrane trafficking

Abstract: Our understanding of fundamental biological processes within platelets is continually evolving. A critical feature of platelet biology relates to the intricate uptake, packaging and release of bioactive cargo from storage vesicles, essential in mediating a range of classical (haemostasis/thrombosis) and non-classical (regeneration/inflammation/metastasis) roles platelets assume. Pivotal to the molecular control of these vesicle trafficking events are the small GTPases of the Ras superfamily, which function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…61,62 Given the absence of ATP8A1 in the 226 JING et al plasma membrane of platelets (Figure 1D), we reason that ATP8A1 is predominantly located in intracellular membranes and is involved in vesicle-mediated trafficking in platelets. Platelets have complete intracellular membrane systems 63 and possess fundamental membrane trafficking processes such as endocytosis. 64 Moreover, upon activation, platelets undergo dramatic shape change 1 and carry out exocytosis such as secretion of procoagulant components and release of granules (dense-/a-granule).…”
mentioning
confidence: 99%
“…61,62 Given the absence of ATP8A1 in the 226 JING et al plasma membrane of platelets (Figure 1D), we reason that ATP8A1 is predominantly located in intracellular membranes and is involved in vesicle-mediated trafficking in platelets. Platelets have complete intracellular membrane systems 63 and possess fundamental membrane trafficking processes such as endocytosis. 64 Moreover, upon activation, platelets undergo dramatic shape change 1 and carry out exocytosis such as secretion of procoagulant components and release of granules (dense-/a-granule).…”
mentioning
confidence: 99%
“…In myocytes, Rab9-dependent autophagosomes recognize and engulf damaged mitochondria, resulting in ischemia-reperfusion (IR) changes in oxidative phosphorylation, eventually decreasing cardiomyocyte viability [ 35 , 36 , 37 ]. In diabetic patients with albuminuria, a genome-wide association study identified a genetic locus of Rab38 associated with albuminuria, highlighting novel pathways influencing albuminuria [ 38 ].…”
Section: Rab-mediated Vesicular Traffic and Diseasesmentioning
confidence: 99%
“…More than 70 members of the Rab family have been identified, and they play specific roles in vesicle trafficking, depending on their cellular locations. 1,2,4 At least 40 Rab proteins are recognized in human platelets, 4 but specific roles in vesicle trafficking are unknown in platelets or megakaryocytes for the majority. RAB31 (Ras-related protein in brain 31), a member of the RAB5 subfamily of Rab GTPases, was cloned from human platelets, 5 and it shared 82% homology with RAB22B protein identified in human melanocytes.…”
Section: Introductionmentioning
confidence: 99%